Toxoplasma gondii strain-dependent effects on mouse behaviour - Kannan, Geetha; Moldovan, Krisztina; Xiao, Jian-Chun; Yolken, Robert H; Jones-Brando, Lorraine; Pletnikov, Mikhail V (Folia parasitologica, 2010)
Toxoplasma gondii reportedly manipulates rodent behaviour to increase transmission to its definitive feline host. We compared the effects of mouse infection by two Type II strains of T. gondii, Prugniaud (PRU) and ME49, on attraction to cat odour, locomotor activity, anxiety, sensorimotor gating, and spatial working and recognition memory 2 months post-infection (mpi). Attraction to cat odour was reassessed 7 mpi. At 2 mpi, mice infected with either strain exhibited significantly more attraction to cat odour than uninfected animals did, but only PRU-infected mice exhibited this behaviour 7 mpi. PRU-infected mice had significantly greater body weights and hyperactivity, while ME49-infected mice exhibited impaired spatial working memory. No differences in parasite antibody titres were seen between PRU- and ME49-infected mice. The present data suggest the effect of T. gondii infection on mouse behaviour is parasite strain-dependent.
Keywords: Toxoplasmosis, Animal; myši; Behavior, Animal; ženské pohlaví; Cats; Mice, Inbred BALB C; zvířata; Mice; Odorants; odoranty; Female; toxoplazmóza zvířat; Toxoplasma; myši inbrední BALB C; chování zvířat; kočky; Animals